Visual Inferential Elements in EFL Learning in Mbujimayi - DIKELELA KAPINGA, Désiré; CIBANGU MBAYA, Patrice; KABUYI KAHAMBA, Patrick (International Journal of Scientific Research and Management (IJSRM), 2023)
The paper focuses on some inferential elements in EFL learning in Mbujimayi. More specifically, the study points out differences occurring in English sound production of /t/, /dʒ/, /ʒ/, /ð/, /v/, and /θ/ by Ciluba speaking learners. After discussing the findings obtained from observation and questionnaire, it has been discovered that the learners’ prior linguistic knowledge justifies the errors they make in this regard, the linguistic patterns of the target language being unfamiliar to them.  To remedy the issue, we suggest three things: (1) attention, implying that the teacher should work to make the learners recognize words so that they can be aware of them as useful language items. (2)  Retrieval, standing for the process indicating that a word may be noticed by the learners and understood in the textual input to the task. (3) Generation, which implies requiring of the learners to use the wanted item in new contexts.